PEMANFAATAN ALGORITMA CLASSIFICATION AND REGRESSION TRESS (CART) UNTUK MEMPREDIKSI OMSET SPANDUK PADA CV.MOEHA ADVERTISING - Alan Bangun Siregar; Efori Buulolo; Permanan Ginting (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2017)
As the development of Information Technology Education World is increasingly going to need a problem to solve a problem in the company that is about an existing turnover, using the method of Classification And Regression Tress (CART), Revenue is an important component in information information in the income statement , When the income is higher than the cost that has been charged then the company. Or if the opposite situation is lower than the cost that has been charged then the company suffered losses, For example CV. Moeha Advertising which produces promotional items banners, seen from the type of materials used, the amount of ink used and the size of the banners to be printed, will be determined the price and number of banners that will be appropriate. The existence of day-to-day operational data activities will increase in number. If left alone, then the transaction data is only a waste that is not meaningful. With the support of technology, the ability to collect and process data.